The Nuclear Receptor Superfamily Has Undergone Extensive Proliferation and Diversification in Nematodes - Sluder, Ann E.; Mathews, Siuyien Wong; Hough, David; Yin, Viravuth P.; Maina, Claude V. (Genome Research, 1999)
The nuclear receptor (NR) superfamily is the most abundant class of transcriptional regulators encoded in the Caenorhabditis elegans genome, with >200 predicted genes revealed by the screens and analysis of genomic sequence reported here. This is the largest number of NR genes yet described from a single species, although our analysis of available genomic sequence from the related nematode Caenorhabditis briggsae indicates that it also has a large number. Existing data demonstrate expression for 25% of theC. elegans NR sequences. Sequence conservation and statistical arguments suggest that the majority represent functional genes. An analysis of these genes based on the DNA-binding domain motif revealed that several NR classes conserved in both vertebrates and insects are also represented among the nematode genes, consistent with the existence of ancient NR classes shared among most, and perhaps all, metazoans. Most of the nematode NR sequences, however, are distinct from those currently known in other phyla, and reveal a previously unobserved diversity within the NR superfamily. In C. elegans, extensive proliferation and diversification of NR sequences have occurred on chromosome V, accounting for > 50% of the predicted NR genes.[The sequence data described in this paper have been submitted to the GenBank data library under accession nos.AF083222–AF083225 and AF083251–AF083234.]
10.1101/gr.9.2.103